Breaking the silence : Zanele's journey to recovery - Payne, Charmaine (Rhodes University, Faculty of Humanities, Department of Psychology, 2007)
This study employed a case-based research design to document the psychological assessment and treatment of Zanele, a 15-year-old black Xhosa speaking female who was raped twice in 2006 by the same perpetrator. The aim of the study was to explore whether, the model for assessment and intervention for posttraumatic stress disorder (PTSD) developed by Ehlers and Clark (2000) was effective and transportable to the South African context. Zanele had a sufficient understanding of English for assessment to proceed without use of an interpreter. She reported a number of PTSD symptoms which were causing her significant distress and had impacted on her social and educational functioning. These included flashbacks of the perpetrator's face when she looked at the faces of black men, nightmares about the traumas she had endured and feeling isolated from others. A number of cognitive techniques were utilised in this study, however the central interventions included working with triggers, imagery rehearsal techniques with a focus on nightmares, and reliving with cognitive restructuring within and outside reliving. Psychoeducation and increasing her social support were also important components of the intervention. Her progress was monitored by means of several self-report measures which were displayed in graphic and tabular form. In addition, a thematically selective narrative of the assessment and first 23 sessions of the intervention was written which documents some of the central processes set in motion by the interventions. These results provide evidence that this model was both effective and transportable to the South African population. In addition, the study demonstrated that it is possible for a white English speaking clinician to work with a black Xhosa speaking individual and make substantial therapeutic gains.
Keywords: Rape victims -- Counseling of -- South Africa; Rape victims -- Counseling of -- South Africa -- Case studies; Post-traumatic stress disorder -- Patients -- Rehabilitation; Post-traumatic stress disorder -- Patients -- Case studies